2018
DOI: 10.1177/1359104518807742
|View full text |Cite
|
Sign up to set email alerts
|

Use of respiratory rates and heart rate variability in the assessment and treatment of children and adolescents with functional somatic symptoms

Abstract: Functional somatic symptoms (FSS) emerge when the stress system is activated in response to physical or emotional stress that is either chronic or especially intense. In such cases, the heightened state of physiological arousal and motor activation can be measured through biological markers. Our team have integrated the use of biological markers of body state – respiratory rate, heart rate (HR) and heart rate variability (HRV) measurements – as a way of helping families to understand how physical symptoms can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The limitations of the study consist in a transversal design and can not establish cause and effect relationships with vasomotor symptoms and HRV. The age group is significantly different between two groups and HRV is an age dependent parameter [41]. However, age is a variable related to menopause transition, which does not make possible to provide subjects with similar ages in similar menopause period.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the study consist in a transversal design and can not establish cause and effect relationships with vasomotor symptoms and HRV. The age group is significantly different between two groups and HRV is an age dependent parameter [41]. However, age is a variable related to menopause transition, which does not make possible to provide subjects with similar ages in similar menopause period.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, HR variability was found to be lower in children and adolescents with functional somatic symptoms that occur when the body responds to physical or emotional stress. 25 While there has not been any testing in cats, this could be a potential way to measure stress during veterinary visits, and even prior to the visit, if the stress of wearing a monitor could be controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Prior HRV-RSA biofeedback studies have shown that an increase of HRV was causally related to several positive effects on psychological parameters. These studies were performed in distinct clinical populations of all ages and variable medical and psychological conditions (Chudleigh et al, 2019; Darling et al, 2019; Gevirtz, 2013; Kennedy & Parker, 2019; Knox et al, 2011; Lehrer et al, 2020; Lehrer & Gevirtz, 2014; Thabrew et al, 2018). In this protocol, individuals practice to breath at their resonant frequency, which can be found between 4.5 and 7 breaths per minute.…”
Section: Background and Rationalementioning
confidence: 99%